Genetic Variability, Heritability, and Genetic Advance Estimates in Garlic (Allium sativum) from the Gamo Highlands of Southern Ethiopia. (21st October 2021) - Tesfaye, Azene
Abstract : Genetic variability is the fundamental requirement for any plant breeding program to develop a superior cultivar. This study aimed to estimate the genetic variability and determine the correlation between the various quantitative characteristics of garlic accessions. The experiment was carried out in the Ezo-Otte area of the Chencha district in the Gamo highlands of southern Ethiopia and 28 garlic accessions were evaluated in a Randomized Complete Block Design with three replicates. Various morphological descriptors were measured to evaluate the variability and correlation coefficients. The analysis of variance showed a highly significant variation for all characters, which indicates greater variability in the accession. High and moderate heritability in broad sense estimates were obtained for the majority of the traits examined. Days to maturity (28.09), bulb weight (22.33), and bulb diameter (equatorial) (21.33) showed higher genetic advance. The maximum value of the genetic progress as a percentage of the mean was observed in bulb yield, clove weight, bulb diameter (equatorial), and number of leaves. In addition, bulb diameter (equatorial), clove weight, bulb weight, and plant height were observed to be highly hereditary coupled with high genetic advance as a percentage of the mean, suggesting that they can be improved by direct selection. Coefficient analysis has shown that maximum attention should be paid to bulb diameter (equatorial), the number of cloves, bulb diameter (equatorial), bulb weight, plant height, and leaf length, as these traits also correlate positively and significantly with bulb yield.